World Peace Postage Association records - World Peace Postage Association
Correspondence of the association's secretary, James Woodburn Hamilton, with peace organizations and postal officials of various nations advocating the issuance of postage stamps promoting world peace.
Collection material in English.
Keywords: Hamilton, James Woodburn, -- 1866-; Peace -- Societies, etc; Peace on postage stamps